Synaptic inhibition regulates associative interactions between afferents during the induction of long-term potentiation and depression. - Tomasulo, R A (1993)
The induction of long-term potentiation and depression depends upon associative interactions between synapses that converge on individual dendrites. The distance over which these associative interactions occur is limited. The present study evaluates whether this limitation is regulated by synaptic inhibition. We evaluated the associative interactions between two inputs that terminate on different proximo-distal locations along the dendrites of dentate granule cells in the presence of the gamma-aminobutyric acid (GABA) antagonist bicuculline methiodide. Local blockade of GABAergic inhibition enhanced associative interactions between nonoverlapping inputs, compared to within-animal control sites, where inhibitory transmission was intact. The results suggest that synaptic inhibition limits interactions between excitatory synapses by creating current shunts that limit the spread of depolarization within the dendritic tree.